Genome editing of soybean inoculant using CRISPR/Cas9 system: enhancing agricultural sustainability - Serantes, Laura (2024)
In modern agriculture, inoculants, consisting of various bacteria and fungi, are essential for promoting crop growth and sustainability while reducing reliance on agrochemicals. Despite their benefts, there have been no recent signifcant advances in enhancing their efcacy. Notably, Bradyrhizobium japonicum E109 and Bradyrhizobium japonicum SEMIA 5079, the most globally utilized, were isolated decades ago, underscoring the need for genetic enhancement. Recently, eforts have focused on selecting spontaneous mutations in genes associated with denitrifcation and oxidative stress. While this technology has shown promise in reducing nitrous oxide emissions and enhancing root colonization, selecting mutants remains costly and challenging without clear phenotypic markers. The CRISPR/Cas9 system ofers a potential solution, although validation is limited to model strains such as Sinorhizobium meliloti 1021. Using the CRISPR/Cas9 system and three sgRNAs, we have edited the genes 16S, napA and glxA from strains E109 and SEMIA5079, generating mutants with streptomycin tolerance, reduced nitrate reductase activity, and increased catalase activity, respectively. Finally, we discuss how the CRISPR/Cas9 system can contribute to bridging the gap between crop and inoculant improvement, and its possible role in producing a new generation of climate-smart inoculants.